Pharmacological Modulation of Radiation Damage. Does It Exist a Chance for Other Substances than Hematopoietic Growth Factors and Cytokines? - Hofer, Michal; Hoferová, Zuzana; Falk, Martin (International journal of molecular sciences, 2017)
In recent times, cytokines and hematopoietic growth factors have been at the center of attention for many researchers trying to establish pharmacological therapeutic procedures for the treatment of radiation accident victims. Two granulocyte colony-stimulating factor-based radiation countermeasures have been approved for the treatment of the hematopoietic acute radiation syndrome. However, at the same time, many different substances with varying effects have been tested in animal studies as potential radioprotectors and mitigators of radiation damage. A wide spectrum of these substances has been studied, comprising various immunomodulators, prostaglandins, inhibitors of prostaglandin synthesis, agonists of adenosine cell receptors, herbal extracts, flavonoids, vitamins, and others. These agents are often effective, relatively non-toxic, and cheap. This review summarizes the results of animal experiments, which show the potential for some of these untraditional or new radiation countermeasures to become a part of therapeutic procedures applicable in patients with the acute radiation syndrome. The authors consider β-glucan, 5-AED (5-androstenediol), meloxicam, γ-tocotrienol, genistein, IB-MECA (N⁶-(3-iodobezyl)adenosine-5'-N-methyluronamide), Ex-RAD (4-carboxystyryl-4-chlorobenzylsulfone), and entolimod the most promising agents, with regards to their contingent use in clinical practice.
Keywords: Hematopoietic System; radiomitigators; cytokiny; hematopoiesis; Cytokines; Animals; acute radiation syndrome; lidé; Radiation-Protective Agents; radioprotektivní látky; Humans; akutní radiační syndrom; zvířata; radioprotectors; Acute Radiation Syndrome; hematopoetický systém